A MoO3 / Fe2(MoO4)3 composite material and its preparation method and application

Through the composite preparation method of MoO3 and Fe2(MoO4)3, a MoO3/Fe2(MoO4)3-x composite catalyst with high photoelectrocatalytic nitrogen reduction synthesis performance was prepared, which solved the problems of poor catalytic performance and low synthesis efficiency of existing photoelectrocatalytic catalysts, and achieved efficient and stable nitrogen reduction synthesis effect.

CN118978186BActive Publication Date: 2025-04-08CHANGAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411051146.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-01
Publication Date
2025-04-08
Estimated Expiration
2044-08-01

AI Technical Summary

Technical Problem

The existing photoelectric catalysts have poor catalytic performance, poor conductivity and low synthesis efficiency in the process of nitrogen reduction synthesis of ammonia.

Method used

By compounding MoO3 with Fe2(MoO4)3, a MoO3/Fe2(MoO4)3-x composite catalyst was prepared, and the electron transfer efficiency and N2 adsorption capacity were improved by using defective structure and heterojunction structure.

Benefits of technology

The efficiency and chemical stability of photoelectric catalytic synthesis of ammonia were significantly improved, with a yield of 2.04 mmol·h-1·gcat-1, a Faraday efficiency of 40%, and the ammonia production efficiency almost did not decrease after 6 cycle tests.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118978186B_ABST
    Figure CN118978186B_ABST
Patent Text Reader

Abstract

The present invention discloses a MoO3 / Fe2(MoO4)3 composite material and its preparation method and application, belonging to the technical field of chemical catalytic materials. The preparation method comprises the following steps: firstly, (NH4)6Mo7O 24 ‧4H2O and Fe(NO3)3·9H2O are dissolved in solvents to obtain solution A and solution B respectively, and then the solutions are mixed and stirred to react; finally, the solid in the reactant is separated, dried, ground, and calcined to obtain Fe2(MoO4)3; Fe2(MoO4)3, PVP and water are mixed evenly, NaBH4 solution is added, stirred, and separated to obtain a solid product; the solid product and (NH4)6Mo7O 24 ‧4H2O is mixed in a solvent, and then continuously stirred and evaporated to dryness to obtain a solid, and the solid is calcined to obtain the obtained composite material. The composite material obtained by the present invention has high photoelectrocatalytic performance, high synthetic ammonia yield, Faraday efficiency and chemical stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of chemical catalytic materials, and in particular to a MoO3 / Fe2(MoO4)3 composite material and a preparation method and application thereof. Background Art

[0002] Ammonia (NH3), as an indispensable chemical raw material for human society, plays an important role in industry and agriculture. However, commercial NH3 synthesis is mainly achieved by the Haber-Bosch (HB) process under harsh reaction conditions (650-750 K, 150-350 bar). The preparation and compression of precursors (H2 and N2) consume about 2% of fossil fuels worldwide, which leads to a large amount of greenhouse gas emissions. Therefore, developing an efficient and sustainable NH3 synthesis route is one of the key topics of concern in today's society. To date, various advanced methods have been proposed to promote the conversion of N2 to NH3, such as biochemical, electrochemical, photocatalytic and photoelectrochemical (PEC); these technologies do not produce a large amount of CO2, especially the photoelectrocatalytic N2 reduction reaction (PEC NRR), which usually exhibits remarkable catalytic performance due to the synergistic effect of photocatalysis and electrochemistry in NH3 synthesis.

[0003] Since N2 is an extremely stable molecule, it is crucial to design photoelectric materials with excellent N2 adsorption / activation capabilities. In recent years, the emergence of abundant reaction sites in photocathode materials has provided new opportunities and challenges for the field of PEC NRR. So far, Fe2O3 has been effective as a catalyst for N2 reduction to ammonia synthesis. In a tandem PEC cell under AM 1.5 G solar irradiation, the ideal efficiency of solar energy conversion is about 15.5%. However, the photoelectrocatalytic performance of α-Fe2O3 is limited by certain factors, such as the high recombination rate of electrons and holes, the low diffusion length of holes (2-4 nm) and poor conductivity, which leads to a large overpotential for light-assisted nitrogen reduction and low efficiency of ammonia synthesis. How to prepare a composite material with multiple composite sites, high photocatalytic performance and conductivity, high selectivity and photoelectrocatalytic efficiency is one of the key issues to be solved in the field of photoelectrocatalytic ammonia synthesis technology. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a MoO3 / Fe2(MoO4)3 composite material and its preparation method and application, so as to solve the problems of poor catalytic performance, poor conductivity and low efficiency of synthetic ammonia of existing photoelectrocatalysts.

[0005] The technical solution of the present invention to solve the above technical problems is as follows:

[0006] A method for preparing a MoO3 / Fe2(MoO4)3 composite material comprises the following steps:

[0007] (1) First, (NH4)6Mo7O 24 ‧4H2O and Fe(NO3)3·9H2O are dissolved in solvents to obtain solution A and solution B respectively, and then solution A and solution B are mixed and stirred continuously to react; finally, the solid in the reactant is separated, dried, ground, and calcined to obtain Fe2(MoO4)3;

[0008] (2) Evenly mix the Fe2(MoO4)3, PVP and water obtained in step (1), add NaBH4 solution, stir and separate to obtain a solid product;

[0009] (3) The solid product obtained in step (2) and (NH4)6Mo7O 24 ‧4H2O is mixed in a solvent, stirred continuously and evaporated to dryness to obtain a solid, which is then calcined to obtain the product.

[0010] The beneficial effects of the present invention are as follows: the present invention successfully compounds MoO3 and Fe2(MoO4)3, and according to the atomic molar ratio of Mo, prepares a MoO3 / Fe2(MoO4)3-x composite catalyst with high photoelectrocatalytic nitrogen reduction and ammonia synthesis performance. Studies have shown that the defective structure reduces the valence band position of Fe2(MoO4)3-x, reduces the free energy of electron transition from MoO3 to Fe2(MoO4)3-x, and is conducive to accelerating the transfer of electrons, thereby further promoting the N2 reduction reaction. Fe2(MoO4)3-x has a strong N2 adsorption effect due to the structural oxygen vacancies, which provides a good foundation for the subsequent breaking of the N≡N triple bond and the hydrogenation reduction step; at the same time, the construction of the heterojunction reduces the recombination of photogenerated electrons and holes, accelerates the charge transfer, and significantly improves the photoelectrocatalytic ammonia synthesis effect.

[0011] Furthermore, in step (1), the volume ratio of solution A to solution B is 0.8-1.2:0.8-1.2.

[0012] Preferably, in step (1), the volume ratio of solution A to solution B is 1:1.

[0013] Furthermore, in solution A, (NH4)6Mo7O 24 The mass volume ratio of 4H2O and solvent is 1 g: 4~8 mL, and the solvent is ethylene glycol; the mass volume ratio of Fe(NO3)3·9H2O and solvent in solution B is 1 g: 5~10 mL, and the solvent is ethylene glycol.

[0014] Furthermore, in step (1), the continuous stirring time is 5 to 10 h; the reaction temperature is 150 to 200°C and the time is 10 to 15 h; the drying temperature is 50 to 70°C and the time is 5 to 10 h; the calcination temperature is 500 to 600°C and the time is 8 to 12 h.

[0015] Preferably, the continuous stirring time in step (1) is 8 h; the reaction temperature is 170° C. and the reaction time is 12 h; the drying temperature is 60° C. and the reaction time is 8 h; and the calcination temperature is 550° C. and the reaction time is 10 h.

[0016] Furthermore, in step (2), the mass ratio of Fe2(MoO4)3 to PVP is 1:1.5-2; the volume ratio of NaBH4 solution to the mixed solution of Fe2(MoO4)3, PVP and water is 1:4-6, and the concentration of NaBH4 solution is 5-100 μmol·L -1 .

[0017] Preferably, in step (2), the mass ratio of Fe2(MoO4)3 to PVP is 1:1.7; the volume ratio of NaBH4 solution to the mixed solution of Fe2(MoO4)3, PVP and water is 1:5.

[0018] Furthermore, in step (2), the NaBH4 solution is added dropwise, and the stirring time is 30-90 min.

[0019] Furthermore, the solid product in step (3), (NH4)6Mo7O 24 ‧The mass volume ratio of 4H2O and solvent is 8~9 g:1g:100-200 mL, and the solvent is ethanol.

[0020] Furthermore, the continuous stirring time in step (3) is 20-30 h; the calcination conditions are: heating at a heating rate of 4-6°C to 500-600°C and calcining for 8-12 h.

[0021] Preferably, the continuous stirring time in step (3) is 24 h; the calcination conditions are: heating to 550° C. at a heating rate of 5° C. and calcining for 10 h.

[0022] A MoO3 / Fe2(MoO4)3 composite material is prepared by adopting the preparation method.

[0023] Application of the above MoO3 / Fe2(MoO4)3 composite material in photoelectrocatalytic synthesis of ammonia.

[0024] The present invention has the following beneficial effects:

[0025] (1) The presence of oxygen vacancies in the MoO3 / Fe2(MoO4)3 composite material prepared by the present invention causes defective energy levels to exist in the band gap of Fe2(MoO4)3, thereby reducing the valence band energy, reducing the band gap width, and improving the light absorption performance; the construction of the MoO3 / Fe2(MoO4)3 heterojunction reduces the recombination of photogenerated electrons and holes, accelerates electron transfer, and promotes the participation of electrons with high reduction potential in the N2 reduction reaction.

[0026] (2) The MoO3 / Fe2(MoO4)3 composite material provided by the present invention is used in synthetic ammonia, and the synthetic ammonia yield can reach 2.04 mmol·h -1 ·g cat -1 And 40% Faradaic efficiency, and the ammonia production efficiency hardly decreased after 6 cycle tests, with good chemical stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is the XRD pattern in Experimental Example 1;

[0028] Figure 2 The UV-visible diffuse reflectance spectra and band gap diagrams in Experimental Example 2, wherein (a) and (c) are spectra, and (b) and (d) are band gap diagrams;

[0029] Figure 3 The nitrogen adsorption-desorption isotherm and pore size distribution diagram in Experimental Example 3, wherein (a) is the nitrogen adsorption-desorption isotherm, and (b) is the pore size distribution diagram;

[0030] Figure 4 It is the linear sweep voltammetry curve in Experimental Example 4;

[0031] Figure 5 is the transient photocurrent diagram in Experimental Example 5;

[0032] Figure 6 The electrochemical impedance diagram in Experimental Example 6;

[0033] Figure 7 The electrochemical ammonia synthesis efficiency and Faraday efficiency diagram in Experimental Example 7;

[0034] Figure 8 This is a graph showing the cycle stability test results at -0.6 V vs. RHE bias voltage in Experimental Example 8. DETAILED DESCRIPTION

[0035] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0036] Embodiment 1:

[0037] A method for preparing a MoO3 / Fe2(MoO4)3 composite material comprises the following steps:

[0038] (1) Preparation of Fe2(MoO4)3

[0039] First, 2.47 g (NH4)6Mo7O 24 ‧4H2O was added to 20 mL ethylene glycol and ultrasonicated for 30 min until it was completely dissolved to obtain solution A. 3.77 g Fe(NO3)3·9H2O was added to 20 mL ethylene glycol and ultrasonicated for 30 min until it was completely dissolved to obtain solution B.

[0040] Then, after solution A and solution B were mixed, the solution turned orange-red, and after continuous stirring for 8 h, an orange-red precipitate appeared in the solution. The stirred mixed solution was transferred to a 100 mL polytetrafluoroethylene liner, the liner was placed in a stainless steel reactor and sealed, and the reactor was placed in a 170°C forced air drying oven for reaction for 12 h;

[0041] Finally, after cooling to room temperature, the reactants were taken out and separated by centrifugation with pure water and ethanol respectively. The obtained solid was dried in an oven at 60°C for 8 h and then fully ground with a mortar. The ground powder was placed in a magnetic boat and calcined at 550°C for 10 h. After cooling to room temperature, brick-red Fe2(MoO4)3 powder was obtained.

[0042] (2) Preparation of Fe2(MoO4)3-x

[0043] 0.592 g of Fe2(MoO4)3 powder obtained in step (1) and 1 g of PVP were added to 100 mL of pure water and ultrasonicated for 30 min to make them dispersed evenly. 20 mL of 10 μmol·L -1 of NaBH4 solution and continued stirring for 1 h before separating the solid to obtain Fe2(MoO4)3-10.

[0044] (3) Preparation of MoO3 / Fe2(MoO4)3 composite materials

[0045] Add 1.478 g of Fe2(MoO4)3-10 prepared in step (2) to 20 mL of ethanol, stir evenly, and then add 0.17 g of (NH4)6Mo7O 24 ‧4H2O, stirred continuously for 24 h and then evaporated at 80℃ to obtain a dry solid. The solid was calcined in a muffle furnace for 6 h at a heating rate of 5℃ / min to obtain the composite material MoO3 / Fe2(MoO4)3-10.

[0046] Embodiment 2:

[0047] A method for preparing a MoO3 / Fe2(MoO4)3 composite material comprises the following steps:

[0048] (1) Preparation of Fe2(MoO4)3

[0049] First, 2.47 g (NH4)6Mo7O 24 ‧4H2O was added to 20 mL ethylene glycol and ultrasonicated for 30 min until it was completely dissolved to obtain solution A. 3.77 g Fe(NO3)3·9H2O was added to 20 mL ethylene glycol and ultrasonicated for 30 min until it was completely dissolved to obtain solution B.

[0050] Then, after solution A and solution B were mixed, the solution turned orange-red, and after continuous stirring for 8 h, an orange-red precipitate appeared in the solution. The stirred mixed solution was transferred to a 100 mL polytetrafluoroethylene liner, the liner was placed in a stainless steel reactor and sealed, and the reactor was placed in a 170°C forced air drying oven for reaction for 12 h;

[0051] Finally, after cooling to room temperature, the reactants were taken out and separated by centrifugation with pure water and ethanol respectively. The obtained solid was dried in an oven at 60°C for 8 h and then fully ground with a mortar. The ground powder was placed in a magnetic boat and calcined at 550°C for 10 h. After cooling to room temperature, brick-red Fe2(MoO4)3 powder was obtained.

[0052] (2) Preparation of Fe2(MoO4)3-x

[0053] 0.592 g of Fe2(MoO4)3 powder obtained in step (1) and 1 g of PVP were added to 100 mL of pure water and ultrasonicated for 30 min to make them dispersed evenly. 20 mL of 30 μmol·L -1 of NaBH4 solution and continued stirring for 1 h before separating the solid to obtain Fe2(MoO4)3-30.

[0054] (3) Preparation of MoO3 / Fe2(MoO4)3 composite materials

[0055] Add 1.478 g of Fe2(MoO4)3-30 prepared in step (2) to 20 mL of ethanol, stir evenly, and then add 0.17 g of (NH4)6Mo7O 24 ‧4H2O, stirred continuously for 24 h and then evaporated at 80℃ to obtain a dry solid. The solid was calcined in a muffle furnace for 6 h at a heating rate of 5℃ / min to obtain the composite material MoO3 / Fe2(MoO4)3-30.

[0056] Embodiment 3:

[0057] A method for preparing a MoO3 / Fe2(MoO4)3 composite material comprises the following steps:

[0058] (1) Preparation of Fe2(MoO4)3

[0059] First, 2.47 g (NH4)6Mo7O 24 ‧4H2O was added to 20 mL ethylene glycol and ultrasonicated for 30 min until it was completely dissolved to obtain solution A. 3.77 g Fe(NO3)3·9H2O was added to 20 mL ethylene glycol and ultrasonicated for 30 min until it was completely dissolved to obtain solution B.

[0060] Then, after solution A and solution B were mixed, the solution turned orange-red, and after continuous stirring for 8 h, an orange-red precipitate appeared in the solution. The stirred mixed solution was transferred to a 100 mL polytetrafluoroethylene liner, the liner was placed in a stainless steel reactor and sealed, and the reactor was placed in a 170°C forced air drying oven for reaction for 12 h;

[0061] Finally, after cooling to room temperature, the reactants were taken out and separated by centrifugation with pure water and ethanol respectively. The obtained solid was dried in an oven at 60°C for 8 h and then fully ground with a mortar. The ground powder was placed in a magnetic boat and calcined at 550°C for 10 h. After cooling to room temperature, brick-red Fe2(MoO4)3 powder was obtained.

[0062] (2) Preparation of Fe2(MoO4)3-x

[0063] 0.592 g of Fe2(MoO4)3 powder obtained in step (1) and 1 g of PVP were added to 100 mL of pure water and ultrasonicated for 30 min to make them dispersed evenly. 20 mL of 50 μmol·L -1 of NaBH4 solution and continued stirring for 1 h before separating the solid to obtain Fe2(MoO4)3-50.

[0064] (3) Preparation of MoO3 / Fe2(MoO4)3 composite materials

[0065] Add 1.478 g of Fe2(MoO4)3-50 prepared in step (2) to 20 mL of ethanol, stir evenly, and then add 0.17 g of (NH4)6Mo7O 24 ‧4H2O, stirred continuously for 24 h and then evaporated at 80℃ to obtain a dry solid. The solid was calcined in a muffle furnace for 6 h at a heating rate of 5℃ / min to obtain the composite material MoO3 / Fe2(MoO4)3-50.

[0066] Embodiment 4:

[0067] A method for preparing a MoO3 / Fe2(MoO4)3 composite material comprises the following steps:

[0068] (1) Preparation of Fe2(MoO4)3

[0069] First, 2.47 g (NH4)6Mo7O 24 ‧4H2O was added to 20 mL ethylene glycol and ultrasonicated for 30 min until it was completely dissolved to obtain solution A. 3.77 g Fe(NO3)3·9H2O was added to 20 mL ethylene glycol and ultrasonicated for 30 min until it was completely dissolved to obtain solution B.

[0070] Then, after solution A and solution B were mixed, the solution turned orange-red, and after continuous stirring for 8 h, an orange-red precipitate appeared in the solution. The stirred mixed solution was transferred to a 100 mL polytetrafluoroethylene liner, the liner was placed in a stainless steel reactor and sealed, and the reactor was placed in a 170°C forced air drying oven for reaction for 12 h;

[0071] Finally, after cooling to room temperature, the reactants were taken out and separated by centrifugation with pure water and ethanol respectively. The obtained solid was dried in an oven at 60°C for 8 h and then fully ground with a mortar. The ground powder was placed in a magnetic boat and calcined at 550°C for 10 h. After cooling to room temperature, brick-red Fe2(MoO4)3 powder was obtained.

[0072] (2) Preparation of Fe2(MoO4)3-x

[0073] 0.592 g of Fe2(MoO4)3 powder obtained in step (1) and 1 g of PVP were added to 100 mL of pure water and ultrasonicated for 30 min to make them dispersed evenly. 20 mL of 70 μmol·L -1 of NaBH4 solution and continued stirring for 1 h before separating the solid to obtain Fe2(MoO4)3-70.

[0074] (3) Preparation of MoO3 / Fe2(MoO4)3 composite materials

[0075] Add 1.478 g of Fe2(MoO4)3-70 prepared in step (2) to 20 mL of ethanol, stir evenly, and then add 0.17 g of (NH4)6Mo7O 24 ‧4H2O, stirred continuously for 24 h and then evaporated at 80℃ to obtain a dry solid. The solid was calcined in a muffle furnace for 6 h at a heating rate of 5℃ / min to obtain the composite material MoO3 / Fe2(MoO4)3-70.

[0076] Comparative Example 1:

[0077] A method for preparing a MoO3 / Fe2(MoO4)3 composite material comprises the following steps:

[0078] (1) Preparation of Fe2(MoO4)3

[0079] First, 2.47 g (NH4)6Mo7O 24 ‧4H2O was added to 20 mL ethylene glycol and ultrasonicated for 30 min until it was completely dissolved to obtain solution A. 3.77 g Fe(NO3)3·9H2O was added to 20 mL ethylene glycol and ultrasonicated for 30 min until it was completely dissolved to obtain solution B.

[0080] Then, after solution A and solution B were mixed, the solution turned orange-red, and after continuous stirring for 8 h, an orange-red precipitate appeared in the solution. The stirred mixed solution was transferred to a 100 mL polytetrafluoroethylene liner, the liner was placed in a stainless steel reactor and sealed, and the reactor was placed in a 170°C forced air drying oven for reaction for 12 h;

[0081] Finally, after cooling to room temperature, the reactants were taken out and separated by centrifugation with pure water and ethanol respectively. The obtained solid was dried in an oven at 60°C for 8 h and then fully ground with a mortar. The ground powder was placed in a magnetic boat and calcined at 550°C for 10 h. After cooling to room temperature, brick-red Fe2(MoO4)3 powder was obtained.

[0082] (2) Preparation of MoO3 / Fe2(MoO4)3 composite materials

[0083] Add 1.478 g of Fe2(MoO4)3 prepared in step (1) to 20 mL of ethanol, stir evenly, and then add 0.17 g of (NH4)6Mo7O 24 ‧4H2O, stirred continuously for 24 h and then evaporated at 80℃ to obtain a dry solid. The solid was calcined in a muffle furnace for 6 h at a heating rate of 5℃ / min to obtain the composite material MoO3 / Fe2(MoO4)3.

[0084] Test Example 1: XRD Analysis

[0085] X-ray diffraction analysis was performed on Fe2(MoO4)3, MoO3 / Fe2(MoO4)3-30 and pure MoO3 obtained in Example 2. The samples were detected using a PANalytical X'Pert PRO X-ray diffraction instrument at a scanning speed of 10° / min and a scanning angle of 10-80°.

[0086] The experimental results are as follows Figure 1 As shown. Figure 1 It can be seen that the peaks of Fe2(MoO4)3 at 13.79°, 15.32°, 20.43°, 21.76°, 22.66°, 22.99°, 24.90°, 25.71°, and 27.50° completely correspond to the (200), (012), (120), (214), (022), (202), (212), (122), and (224) crystal planes of the standard card PDF#83-1701, indicating the successful preparation of the material. The diffraction peaks of MoO3 at 23.33°, 25.698°, 25.88°, 27.32°, 33.76°, and 38.9° completely correspond to the (110), (040), (120), (021), (111), and (060) crystal planes of the standard card PDF#76-1003. The Fe2(MoO4)3 / MoO3-30 composite material has all the peaks corresponding to the two substances, indicating the successful preparation of the material.

[0087] Test Example 2: UV-Vis Diffuse Reflectance Analysis

[0088] Pure MoO3, Fe2(MoO4)3 prepared in Example 1, Fe2(MoO4)3-10, Fe2(MoO4)3-30, Fe2(MoO4)3-50, Fe2(MoO4)3-70 prepared in Examples 1-4, MoO3 / Fe2(MoO4)3-30 prepared in Example 2 and MoO3 / Fe2(MoO4)3 prepared in Comparative Example 1 were characterized by measuring the UV-visible diffuse reflectance spectra of the above samples in the spectral range of 200-800 nm with barium sulfate as the reference using an Agilent Cary 100 UV spectrophotometer.

[0089] The experimental results are as follows Figure 2 As shown, from Figure 2It can be seen that MoO3 absorbs light in the wavelength range of 300-450 nm, Fe2(MoO4)3 absorbs light in the range of 300-630 nm, MoO3 / Fe2(MoO4)3 and MoO3 / Fe2(MoO4)3-30 absorb light in the range of 300-800 nm, and the absorption intensity in the range of 300-800 nm is greatly improved compared with MoO3 and Fe2(MoO4)3. It is worth noting that the light absorption of MoO3 / Fe2(MoO4)3-30 is higher than that of MoO3 / Fe2(MoO4)3 in the range of 480-800 nm. Fe2(MoO4)3-x containing different amounts of oxygen vacancies responds differently to light. In the range of 300-800 nm, Fe2(MoO4)3-30 has the largest light absorption range and the highest absorption intensity.

[0090] like Figure 2 As shown in Figures (b) and (d), the band gaps of MoO3 and Fe2(MoO4)3 are 2.80 eV and 2.87 eV, respectively. When different amounts of oxygen vacancies are introduced, the band gaps are narrowed to varying degrees, and the band gap of Fe2(MoO4)3-30 changes the most, which is 2.30 eV. Therefore, Fe2(MoO4)3-30 exhibits strong light absorption performance and a wide light absorption range. It is possible to generate more photogenerated carriers under irradiation, which is conducive to the photoexcitation of valence band electrons to the conduction band, thereby participating in the subsequent nitrogen reduction reaction.

[0091] Test Example 3: Adsorption isotherm and specific surface area and pore size distribution analysis

[0092] The adsorption isotherms, specific surface areas and pore size distribution of Fe2(MoO4)3, Fe2(MoO4)3-30 and MoO3 / Fe2(MoO4)3-30 prepared in Example 2 were analyzed using an instrument of model Micromeritics ASAP 2460.

[0093] The experimental results are as follows Figure 3 As shown. Figure 3 It can be seen that all samples showed H3 type hysteresis curves, proving that these three electrode materials have mesoporous structures. The average pore sizes of Fe2(MoO4)3, Fe2(MoO4)3-30, and MoO3 / Fe2(MoO4)3-30 were 17.63, 12.2, and 16.04 nm, respectively. According to the Brunauer-Emmett-Teller (BET) method, the specific surface areas of Fe2(MoO4)3, Fe2(MoO4)3-30, and MoO3 / Fe2(MoO4)3-30 electrode materials were 7.29, 13.35, and 35.12 m 2 g -1The creation of oxygen vacancies and the compounding of materials increase the specific surface area of ​​Fe2(MoO4)3. The larger specific surface area increases the reactive sites, which is beneficial to the adsorption and reaction of N2. The pore size distribution obtained by the Barrett-Joyner-Halenda (BJH) method ( Figure 3 Figure (b) shows that the pores of Fe2(MoO4)3, Fe2(MoO4)3-30 and MoO3 / Fe2(MoO4)3-30 electrode materials are mainly mesopores.

[0094] Test Example 4: Photoresponse performance measurement

[0095] The LSV curves of Fe2(MoO4)3, Fe2(MoO4)3-30, MoO3 / Fe2(MoO4)3-30 prepared in Example 2, MoO3 / Fe2(MoO4)3 prepared in Comparative Example 1 and pure MoO3 were measured, i.e., the linear scanning voltammetric curves of the composite electrodes. The tests were carried out using an electrochemical workstation model CHI6503, using a three-electrode system, with the Ag / AgCl electrode as the reference electrode, the platinum electrode as the counter electrode, and the test sample as the working electrode.

[0096] The experimental results are as follows Figure 4 As shown. Figure 4 It can be seen that the voltages of Fe2(MoO4)3, MoO3, MoO3 / Fe2(MoO4)3, Fe2(MoO4)3-30, and MoO3 / Fe2(MoO4)3-30 at -1.2 V vs. RHE are -0.15, -1.04, -3.02, -4.98, and -6.22 mA·cm, respectively. -2 The photocurrent of MoO3 / Fe2(MoO4)3-30 is 41.5 and 5.98 times that of pure Fe2(MoO4)3 and pure MoO3.

[0097] Test Example 5: Photosensitivity measurement

[0098] The photosensitivity of Fe2(MoO4)3, Fe2(MoO4)3-30, MoO3 / Fe2(MoO4)3-30 prepared in Example 2, MoO3 / Fe2(MoO4)3 prepared in Comparative Example 1 and pure MoO3 were measured by using an electrochemical workstation model CHI6503 to determine the It curve.

[0099] The experimental results are as follows Figure 5 As shown. Figure 5 It can be seen that the instantaneous current density of the MoO3 / Fe2(MoO4)3-30 photocatalytic material when the light is turned on and off is 5 µA·cm -2The TPR value of Fe2(MoO4)3-30 is smaller: 4.03 µA·cm -2 The TPR values ​​of Fe2(MoO4)3, MoO3, and MoO3 / Fe2(MoO4)3 are very low, which are 2.32 µA·cm -2 , 1.05 µA·cm -2 , 0.98 µA·cm -2 .

[0100] Test Example 6: Electrochemical Impedance Spectroscopy Measurement

[0101] Electrochemical impedance spectroscopy was performed on Fe2(MoO4)3, Fe2(MoO4)3-30, MoO3 / Fe2(MoO4)3-30 prepared in Example 2, MoO3 / Fe2(MoO4)3 prepared in Comparative Example 1 and pure MoO3 to test the carrier migration and separation dynamics of the electrode. Generally, the smaller the radius of the electrochemical impedance spectroscopy, the greater the photogenerated electron-hole transfer rate.

[0102] The experimental results are as follows Figure 6 As shown. Figure 6 It can be seen that Fe2(MoO4)3 has the largest radius. After compounding with MoO3, the radius of the electrochemical impedance spectrum of MoO3 / Fe2(MoO4)3 becomes smaller, indicating that the construction of the MoO3 heterojunction increases the reaction kinetics and improves the carrier transfer efficiency. The radius of Fe2(MoO4)3-30 is smaller than that of Fe2(MoO4)3, and even smaller than that of MoO3 / Fe2(MoO4)3, indicating that the structure of oxygen vacancies improves the electron capture ability of Fe2(MoO4)3, reduces the recombination of electrons and holes to a certain extent, and is conducive to the participation of holes in subsequent reactions. The radius of MoO3 / Fe2(MoO4)3-30 is the smallest, indicating that the synergistic effect of the heterojunction and defective oxygen vacancies improves the reaction kinetics.

[0103] Test Example 7: Photocatalytic activity measurement

[0104] The photoelectrocatalytic ammonia synthesis performance of the samples was studied using nitrogen as the nitrogen source, a xenon lamp to simulate sunlight, and 1 mol / L KOH as the electrolyte. The test samples were Fe2(MoO4)3, Fe2(MoO4)3-30, MoO3 / Fe2(MoO4)3-30 prepared in Example 2, MoO3 / Fe2(MoO4)3 prepared in Comparative Example 1, and pure MoO3. Before the reaction, nitrogen was pre-passed into the cathode cell for 0.5 h to 1 h to form a nitrogen-saturated KOH solution, and then constant potential electrolysis was performed (nitrogen reduction reaction and hydrogen evolution reaction occurred at the cathode, and oxygen evolution reaction occurred at the anode) for 2 h, the stirring speed was set to 400 rpm, and the sample was tested after 2 h of reaction to obtain its yield.

[0105] The experimental results are as follows Figure 7 When the bias voltage is -0.6 V vs. RHE, the ammonia synthesis efficiencies of Fe2(MoO4)3, MoO3, MoO3 / Fe2(MoO4)3, Fe2(MoO4)3-30, and MoO3 / Fe2(MoO4)3-30 are 0.30, 0.85, 1.08, 1.36, and 2.04 mmol·h, respectively. -1 ·g cat -1 , and the Faraday efficiency is: 19.02%, 3.40%, 1.28%, 8.86%, 43.00%. The ammonia synthesis efficiency and Faraday efficiency of MoO3 / Fe2(MoO4)3-30 are 6.8 times and 2.26 times that of Fe2(MoO4)3, respectively. The ammonia synthesis efficiency and Faraday efficiency of MoO3 / Fe2(MoO4)3-30 are 2.4 times and 12.65 times that of MoO3, respectively. The heterojunction formed by MoO3 and Fe2(MoO4)3-30 regulates the carrier transport channel, which is beneficial to the separation of electrons and holes and improves the efficiency of ammonia synthesis.

[0106] Test Example 8: Stability Determination

[0107] The MoO3 / Fe2(MoO4)3-30 composite material prepared in Example 2 was subjected to a stability test, and six cycles of ammonia synthesis experiments were carried out under the same conditions as in Experimental Example 7.

[0108] like Figure 8 As shown, after 6 cycles of 2h nitrogen reduction reaction to synthesize ammonia using MoO3 / Fe2(MoO4)3-30 as the photoelectrocatalyst at a bias voltage of -0.6 V vs. RHE, the ammonia yield of the catalyst remained stable at ~98%.

[0109] In summary, the present invention successfully composites MoO3 and Fe2(MoO4)3, and prepares a MoO3 / Fe2(MoO4)3-x composite catalyst with high photoelectrocatalytic nitrogen reduction to ammonia synthesis performance according to the molar ratio of Mo atoms. Studies have shown that the defective structure reduces the valence band position of Fe2(MoO4)3-x, reduces the free energy of electron transition from MoO3 to Fe2(MoO4)3-x, and is conducive to accelerating the transfer of electrons, thereby further promoting the N2 reduction reaction. Fe2(MoO4)3-x has a strong N2 adsorption effect due to the structural oxygen vacancies, which provides a good foundation for the subsequent breaking of the N≡N triple bond and the hydrogenation reduction step; at the same time, the construction of the heterojunction reduces the recombination of photogenerated electrons and holes and accelerates the charge transfer, so the photoelectrocatalytic ammonia synthesis effect of MoO3 / Fe2(MoO4)3-x is significantly improved.

[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a MoO3 / Fe2(MoO4)3 composite material, characterized in that: The following steps are involved: (1) First, (NH4)6Mo7O 24 ‧4H2O and Fe(NO3)3·9H2O are dissolved in solvents to obtain solution A and solution B respectively, and then solution A and solution B are mixed and stirred continuously to react; finally, the solid in the reactant is separated, dried, ground, and calcined to obtain Fe2(MoO4)3; (2) Evenly mix the Fe2(MoO4)3, PVP and water obtained in step (1), add NaBH4 solution, stir and separate to obtain a solid product; (3) The solid product obtained in step (2) and (NH4)6Mo7O 24 ‧4H2O is mixed in a solvent, stirred continuously and evaporated to dryness to obtain a solid, which is then calcined to obtain the product.

2. The method for preparing the MoO3 / Fe2(MoO4)3 composite material according to claim 1, characterized in that: In the step (1), the volume ratio of solution A to solution B is 0.8-1.2:0.8-1.

2.

3. The method for preparing the MoO3 / Fe2(MoO4)3 composite material according to claim 1 or 2, characterized in that: In solution A, (NH4)6Mo7O 24 The mass volume ratio of Fe(NO3)3·9H2O to the solvent is 1 g: 4~8 mL, and the solvent is ethylene glycol; the mass volume ratio of Fe(NO3)3·9H2O to the solvent in solution B is 1 g: 5~10 mL, and the solvent is ethylene glycol.

4. The method for preparing the MoO3 / Fe2(MoO4)3 composite material according to claim 1, characterized in that: In the step (1), the continuous stirring time is 5 to 10 h; the reaction temperature is 150 to 200° C. and the time is 10 to 15 h; the drying temperature is 50 to 70° C. and the time is 5 to 10 h; the calcination temperature is 500 to 600° C. and the time is 8 to 12 h.

5. The method for preparing the MoO3 / Fe2(MoO4)3 composite material according to claim 1, characterized in that: In step (2), the mass ratio of Fe2(MoO4)3 to PVP is 1:1.5-2; the volume ratio of NaBH4 solution to the mixed solution of Fe2(MoO4)3, PVP and water is 1:4-6, and the concentration of NaBH4 solution is 5-100 μmol·L -1 .

6. The method for preparing the MoO3 / Fe2(MoO4)3 composite material according to claim 1, characterized in that: In the step (2), the NaBH4 solution is added dropwise, and the stirring time is 30-90 min.

7. The method for preparing the MoO3 / Fe2(MoO4)3 composite material according to claim 1, characterized in that: The solid product in step (3), (NH4)6Mo7O 24 ‧The mass volume ratio of 4H2O and solvent is 8~9 g:1 g:100-200 mL, and the solvent is ethanol.

8. The method for preparing the MoO3 / Fe2(MoO4)3 composite material according to claim 1, characterized in that: The continuous stirring time in step (3) is 20-30 h; the calcination conditions are: heating at a heating rate of 4-6°C to 500-600°C and calcining for 8-12 h.

9. A MoO3 / Fe2(MoO4)3 composite material, characterized in that: The method is prepared according to any one of claims 1 to 7.

10. Use of the MoO3 / Fe2(MoO4)3 composite material according to claim 9 in photoelectrocatalytic synthesis of ammonia.

Citation Information

Patent Citations

  • Beaded iron molybdate nanofiber photocatalyst as well as preparation method and application

    CN111945249A

  • Synthesis method of oxygen-vacancy-rich ruthenium / nickel molybdate material and application of oxygen-vacancy-rich ruthenium / nickel molybdate material in hydrogen evolution reaction in seawater

    CN116855996A